PENERAPAN KURIKULUM NAHWU METODE KALAMUNA AL-ULA PP AL-LATHIFIYYAH 1 BAHRUL ULUM TAMBAKBERAS JOMBANG - Chotimah, Chusnul; Nurdiana, Laila (JoEMS (Journal of Education and Management Studies), 2021)
The purpose of this research on the nahwu method of the Kalamuna Al Ula method is to find out the application of the nahwu method teaching which was developed by one of the teachers of the Al-Lathifiyyah 1 Bahrul Ulum Islamic Boarding School himself which since 2019 has been applied to explore the science of nahwu accompanied by direct practice on the application of accelerated reading of the book yellow for students. This research method is descriptive qualitative, namely research proposed to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions and thoughts of people, both individually and in groups. The data analysis technique here, the researcher uses the method of observation, interviews and documentation. The results of this study that in the practice of learning nahwu the Kalamuna Al Ula method is presented in the form of sentence amtsilah, discussion, rules. For material exercises as stabilization, each material is completed orally. Among them: students are able to briefly explain what the essence of the chapter discussion is, determine sentences, mention example sentences, sentence structure, store words in the right sentences. The supporting factor of this method is that the chapters are laid out in a systematic way, examples are taken from general mufrodat so that they are easy to understand, especially for beginners And the inhibiting factor of this method is that it prioritizes memorization so that it makes students feel burdened, there are no practice questions written in the book so that students cannot practice questions independently.